Impact of platelet-derived mitochondria transfer in the metabolic profiling and progression of metastatic MDA-MB-231 human triple-negative breast cancer cells - Cereceda, Lucas; Cardenas, J. Cesar; Khoury, Maroun; Silva-Pavez, Eduardo; Hidalgo, Yessia (Frontiers in Cell and Developmental Biology, 2024)
An active role of platelets in the progression of triple-negative breast cancer (TNBC) cells has been described. Even the role of platelet-derived extracellular vesicles on the migration of MDA-MB-231 cells has been reported. Interestingly, upon activation, platelets release functional mitochondria into the extracellular environment. However, the impact of these platelet-derived mitochondria on the metabolic properties of MDA-MB-231 cells remains unclear. We have shown that platelet-derived mitochondria can be internalized by MDA-MB-231 cells in co-culture with platelets, increasing ATP production, oxygen (O2) consumption rate (OCR), cell proliferation, and metabolic adaptability. Additionally, we observed that MDA-MB-231 cells depleted from mitochondrial DNA (mtDNA) can recover cell proliferation in uridine/pyruvate-free cell culture medium and restore mitochondrial O2 consumption after co-culture with platelets, indicating a reconstitution of mtDNA facilitated by platelet-derived mitochondria. In conclusion, our study provides new insights into the role of platelet-derived mitochondria in the metabolic adaptability and progression of metastatic MDA-MB-231 TNBC cells.